Front Cover. Issue 12 (December 2016) - Giakoumi, Sylvaine; Guilhaumon, François; Kark, Salit; Terlizzi, Antonio; Claudet, Joachim; Felline, Serena; Cerrano, Carlo; Coll, Marta; Danovaro, Roberto; Fraschetti, Simonetta; Koutsoubas, Drosos; Ledoux, Jean‐Batiste; et al.
Abstract : The cover image, by Sylvaine Giakoumi et al ., is based on the Biodiversity Research Space invaders; biological invasions in marine conservation planning, DOI:10.1111/ddi.12491 . Photo Credit: Yiannis Issaris.